2017
DOI: 10.3390/e19050196
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic Analysis of Brain Dynamics Detects Negative Stress

Abstract: Abstract:The electroencephalogram (EEG) is the most common tool used to study mental disorders. In the last years, the use of this recording for recognition of negative stress has been receiving growing attention. However, precise identification of this emotional state is still an interesting unsolved challenge. Nowadays, stress presents a high prevalence in developed countries and, moreover, its chronic condition often leads to concomitant physical and mental health problems. Recently, a measure of time serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…In another work, a decrease of relative power in subjects facing a series of distressful stimuli was also described (Bastos Filho et al, 2012). Finally, the fact that this trend is maintained throughout the different time-lags reinforces a previous study where no lag was applied (Garćıa-Mart́ınez et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In another work, a decrease of relative power in subjects facing a series of distressful stimuli was also described (Bastos Filho et al, 2012). Finally, the fact that this trend is maintained throughout the different time-lags reinforces a previous study where no lag was applied (Garćıa-Mart́ınez et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…However, only a few of them have analyzed this phenomena from a non-linear point of view (García-Martínez et al, 2016). Recently, another approach reported that symbolic analysis of brain dynamics was able to detect distress (Garćıa-Mart́ınez et al, 2017). In that study, PE and its extension called AAPE were used to assess brain dynamics for each EEG channel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, little attention has been paid so far to PE of the RRI time series for emotion recognition. To the best of our knowledge, the research developed by García-Martínez et al [23] is the only one in which this symbolic entropic measure has been considered for automatic recognition of emotions. More precisely, EEG records have been analyzed for discerning between emotions of calm and stress.…”
Section: Introductionmentioning
confidence: 99%